FATAL ABUSE AND LEGAL CONSEQUENCES: A CASE STUDY OF DECISION NUMBER 29/Pid.B/2023/PN Gns - Wirayuda Yana, I Komang; Zaini, Zulfi Diane (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This research explores the phenomenon of abuse as a persistent social issue, focusing on the legal regulation and accountability of perpetrators as outlined in Article 351 of the Criminal Code. Specifically, it examines the factors contributing to abuse resulting in fatal outcomes and the legal consequences for perpetrators, using decision number 29/Pid.B/2023/PN Gns as a case study. The study adopts a normative juridical method to analyze the provisions of Law Number 1 of 1964 concerning the Criminal Code. It employs both normative and empirical juridical approaches, combining library research with field data collection through observations and interviews. Data analysis is conducted qualitatively, utilizing primary, secondary, and tertiary data sources. The research identifies situational and emotional factors, particularly jealousy, as primary causes of abuse leading to the victim's death. In the analyzed case, the Panel of Judges at the Gunungsugih Class 1 B District Court sentenced the perpetrator to six years of imprisonment, underscoring the accountability mechanisms enforced by the judicial system. This study provides a nuanced understanding of the interplay between emotional and situational triggers in abuse cases and the application of Article 351 in judicial decisions. By focusing on a specific case, it offers a detailed analysis of the legal process and its outcomes in addressing fatal abuse incidents. The findings highlight the need for targeted interventions to address emotional triggers, such as jealousy, and to enhance public awareness of the legal repercussions of abuse. Additionally, the study underscores the importance of rigorous application and interpretation of legal provisions to ensure justice and deterrence in cases of abuse.